Insufficient future liver remnant and preoperative cholangitis predict perioperative outcome in perihilar cholangiocarcinoma. Issue 1 (January 2021) - Bednarsch, Jan; Czigany, Zoltan; Lurje, Isabella; Amygdalos, Iakovos; Strnad, Pavel; Halm, Paul; Wiltberger, Georg; Ulmer, Tom F.; Schulze-Hagen, Maximilian; Bruners, Philipp; Neumann, Ulf P.; Lurje, Georg
Abstract: Background: Major liver resection has evolved as the mainstay of treatment for patients with perihilar cholangiocarcinoma (pCCA). Here we assessed the suitability of preoperative future liver remnant (FLR) measurement to predict perioperative complications, since surgical morbidity and mortality are high compared to other malignancies. Methods: Between 2011 and 2016, 91 patients with pCCA underwent surgery in curative intent at our institution. The associations of surgical complications with FLR and clinico-pathological characteristics were assessed using logistic regression analyses. Different methods of FLR assessment, the calculated-FLR (cFLR; ratio of FLR to total liver volume), standardized FLR (sFLR; ratio of FLR to liver volume estimated by body surface area) and FLR to bodyweight ratio (FLR/BW) were tested for validity. Results: Multivariable analysis identified preoperative cholangitis (Exp(B) = 0.236; p = 0.030) as the single significant predictor of postoperative mortality and cFLR (Exp(B) = 0.009, p = 0.004) as the single significant predictor of major postoperative morbidity (Clavien-Dindo ≥ 3b). Based on these findings we designed a futility criterion (cFLR<40% OR preoperative cholangitis) predicting in-house mortality. Conclusions: In patients with pCCA, the preoperative FLR<40% as well as preoperative cholangitis are two risk factors to independently predict perioperative morbidity and mortality. The cFLR should be the preferred method of liver volumetry.